The Routine Application of Tumor-Treating Fields in the Treatment of Glioblastoma WHO° IV - Krigers, Aleksandrs; Pinggera, Daniel; Demetz, Matthias; Kornberger, Lisa-Marie; Kerschbaumer, Johannes; Thomé, Claudius; Freyschlag, Christian F. (Frontiers in Neurology, 2022)
Introduction. Tumor-treating fields (TTF) are a specific local oncological treatment modality in glioblastoma multiforme WHO °IV (GBM). Their mechanism of action is based on the effect of electrical fields interfering with the mitotic activity of malignant cells. Prospective studies have demonstrated efficacy, but TTF benefits are still controversially discussed. This treatment was implemented in our center as standard of care in January 2016. We thus discuss the current state of the art as well as our long-term experience in the routine application of TTF. Methods. The data of 48 patients suffering from GBM and treated with TTF was assessed and compared with previously published studies. Up-to-date information from open sources was evaluated. Results. 31 males and 17 females harboring a GBM were treated with TTF between January 2016 and August 2021 in our center. In 98% of cases, TTF were started within 6 weeks after concomitant radiochemotherapy (Stupp protocol). Mean overall survival was 22.6 months (CI95%: 17.3 – 27.9). Current indications, benefits and restrictions were evaluated. Future TTF opportunities and ongoing studies were reviewed. Conclusion. TTF are a feasible and routinely appliable specific oncological treatment option for glioblastoma multiforme WHO °IV. Further research is ongoing to extend the indications and the efficacy of TTF.